The effect of club ownership structure on athletic performance and financial results : Evidence from the English Premier League - Niemi, Niklas (My University, 2025)
The tension between profit and purpose in organizations has been explored in an increasing body of literature in recent years. While traditional business theory, i.e., Friedman's shareholder primacy view, emphasizes profit maximization as the most important organizational goal, increasing perspectives, such as social impact, sustainability, or stakeholder well-being, have been at the core of emerging broader organizational missions. The tension between profit and purpose is often structurally embedded in the company's ownership model, not being only a question of internal organizational values. This theoretical linkage is particularly relevant in the context of professional sports organizations, where financial performance has historically been a secondary priority after athletic success. The objective of this study is to investigate the relationship between various ownership models and the athletic and financial performance of English Premier League (EPL) clubs. The research question of the study, "How are different ownership models associated with athletic performance and financial performance among English Premier League clubs?" seeks to address the gap in research on examining different ownership models based on the geographic origin of the owner association, and their impact on both performance outcomes, athletic and financial. A quantitative regression analysis using Ordinary Least Squares (OLS) was conducted to examine the relationships between ownership structures and performance outcomes. The data was collected over the last ten years, with access to all financial information (2013-2023), and only took into account seasons the club played in the highest division of English football (EPL). The six different ownership categories were transformed into dummy variables and examined in two separate regression equations, focusing on athletic performance and financial results. The position in the league table determined athletic performance after each season, where the financial results variable was constructed from six different characteristics representing different areas of financial health. Overall, the results presented a multifaceted picture. The Stock market model (reference category) was strongly associated with athletic performance but significantly weaker in terms of financial results. The generalizability of the study was restricted due to having only one Stock market in the examination period. Foreign ownerships (American, Eastern, and European) had the most stable joint relationship with performance outcomes, whereas Domestic and Multi-ownership conform to the pattern of Foreign ownership but with a more volatile habit. The case-based insights beyond the regression and theoretical frameworks, i.e., economic theory of professional sports clubs and agency theory, provided additional views and lenses to the results. The observed differences across ownership models should not be interpreted as direct effects, but rather as correlations that unobserved factors may influence. Although Foreign ownership showed the most stable joint results, the differences between the categories can be considered relatively small, and therefore, neither of the ownership models consistently outperformed the others over both performance metrics. This thesis contributes to the academic discussion of sports business by refining and updating the categorization of ownership models, thereby increasing novelty and providing information for the management of sports clubs, owners, regulators, fans, gamblers, and individuals generally interested in the topic. The findings highlight that to promote long-term success, financial stability, and competitiveness, stakeholders must consider how the ownership structure influences both athletic performance and financial sustainability, especially under evolving regulations such as the Profit and Sustainability Rules.
Keywords: sport business, football, English Premier League, ownership structures, athletic performance, financial performance